A Comparative Study on the Clinical Effects of Short-term and Long-term Spinal Cord Stimulation in Patients with Prolonged Disorders of Consciousness - SUN Fengqiao; NIU Hongchuan; YANG Yi; HE Jianghong; ZHAO Yuanli (Xiehe Yixue Zazhi)
ObjectiveTo compare the therapeutic effects of short-term spinal cord stimulation (stSCS) and long-term spinal cord stimulation (ltSCS) on patients with prolonged disorders of consciousness(pDoC).MethodsClinical data of patients with pDoC who underwent SCS surgery at Peking University International Hospital from January 2020 to December 2021 were retrospectively included. Patients were divided into the stSCS group and the ltSCS group based on the surgical approach. The Coma recovery scale-revised (CRS-R) was used to assess the level of consciousness before and 3 months after SCS treatment. Based on CRS-R scores, the clinical diagnosis of the patient's level of consciousenss was categorized into four levels: vegetative state, minimally conscious state minus (MCS-), MCS plus (MCS+), and emergence from the minimally conscious state(EMCS). Improvement in the clinical diagnostic level of consciousness was defined as effective treatment, and the therapeutic outcomes of the stSCS and ltSCS groups were compared.Results44.8% of patients with pDoC showed improvement in their clinical diagnostic level of consciousness after SCS treatment. Compared to preoperative scores, the CRS-R scores at 3 months postoperatively were significantly increased in both the stSCS and ltSCS groups (both P < 0.05). However, there was no significant difference in clinical efficacy between the ltSCS and stSCS groups (P=0.613).ConclusionsBoth stSCS and ltSCS can significantly improve the level of consciousness in patients with pDoC. Compared to ltSCS, stSCS may achieve comparable short-term therapeutic outcomes.